DEVELOPMENT OF THE KETUPAT VILLAGE TOURISM OBJECT BASED ON COMMUNITY RESPONSE IN BANJARMASIN CITY - Adyatma, Sidharta; Munthomimmah, Siti; Arisanty, Deasy; Hastuti, Karunia Puji; Angriani, Parida (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Tourism development in each region is closely related to economic development in order to obtain income or foreign exchange for the region and country. The research aims to analyze the development of Kampung Ketupat tourist attractions based on community responses in Banjarmasin City. The research method uses a quantitative descriptive method, with a sample size of 313 people using a questionnaire with a purposive random sampling technique, and the tourism object components consist of attractions, amenities, and accessibility and are analyzed using a Likert scale. The results of the research show that in the tourism aspect, the respondents agree with the attraction aspect, which is expected to be able to attract tourists and open up employment opportunities; the respondents strongly agree with the amenities aspect because the completeness, cleanliness, and tidiness of the facilities offered are excellent, such as not being allowed to bring food from outside which is afraid of increasing waste, Within the tourist attraction there is a place for people to sell food and drinks. The accessibility aspect of respondents agrees because the road access to Kampung Ketupat is via the river and land routes, which are easy to access, and there is adequate parking space for 2-wheeled and 4-wheeled vehicles.